Participatory community-based farm diversification and nutrition education approach to increase farm, market and dietary diversity in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Based on promising results from pilot (https://doi.org/10.1111/mcn.12803), approach was repeated in a second phase (2018-2020) with new communities in Vihiga County. External evaluation report mentions how this approach has influenced the Vihiga County Nutrition Action Plan. Discussions are ongoing between Bioversity and County governor on how to scale the results.